Analysis of Ḥadīths on Raw Materials for Clothing in the Implementation of Halal Fashion - Fasthabiqul Ambiya Harahap; Fadhillah Is; Rahmi Syahriza; Muhammad Ibrahim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
The global halal fashion industry has expanded rapidly, yet existing halal standards remain largely focused on modest design and body coverage, paying limited attention to the Islamic legal status of textile materials, animal-derived fibers, tanning processes, and material purity. Consequently, the normative foundations of halal fashion require further examination from the perspective of Prophetic traditions. This study aims to analyze the ḥadīths concerning clothing materials as a normative basis for developing a more comprehensive halal fashion framework. Employing library research with a qualitative descriptive-analytical design, the study applies takhrīj al-ḥadīth, isnād and matn criticism, sharḥ analysis, and comparative evaluation of juristic opinions within a maqāṣid al-sharīʿah framework. The analysis focuses on authentic traditions concerning three themes: the prohibition of silk for men, regulations on animal skins and tanning, and ethical guidance on garment cleanliness, color, and length. The findings demonstrate that the examined traditions provide coherent legal and ethical principles governing the permissibility, purity, and proper use of clothing materials. Interpreted through the objectives of Islamic law, these traditions promote the protection of religion (ḥifẓ al-dīn), human well-being (ḥifẓ al-nafs), and property (ḥifẓ al-māl). This study contributes to contemporary halal fashion scholarship by integrating thematic ḥadīth analysis with the maqāṣid al-sharīʿah approach, offering a more comprehensive normative framework for halal textile standards.